Relationship of Socio-economic Profile of the Turmeric Growing Farmers to their Training Need - Anil Kumar , A.K. Paswan , M. N. Ansari; A. K.Singh (Indian Journal of Extension Education, 2016)
A study on training needs of turmeric growers in Samastipur and Muzaffarpur district of Bihar was undertaken. The findings revealed that majority of turmeric growers belong to the advance age group, literate, possessing small size of land holding, low income group. The maximum per cent age of respondents has medium economic motivation, crop intensity and level of knowledge. The results revealed that training need in plant protection measure was given top priority. The other important areas of cultivation in which turmeric growers have shown their desire were high yielding variety, fungicidal seed treatment, sowing method, sowing time and fertilizer management. The most important factors influencing the training needs of turmeric growers in relation to turmeric production were cropping intensity, economic motivation and knowledge which were found to be positively and significantly associated with the training need of turmeric growers. These factors should be kept in view while formulating any training programme. The other independent variables such as family education, size of land holding and area under turmeric cultivation were not able to create such positive correlation as in the case of other selected independent variables.